Comparative analysis of the profitability of small-scale monoculture and diversified yellow corn farms in Cabagan, Isabela, Philippines - Bauita, Angelyn A; Bugas, Jayrald D; Saguibo, Vanessa C; Yago, Airish Lou B; Calubaquib, Michelle Ann M (Asian Journal of Agriculture and Rural Development, 2025)
The study aimed to compare the profitability of small-scale monoculture and diversified yellow corn production farms in Cabagan, Isabela, while also characterizing the socio-demographic profiles of farmers and determining their farming practices. Using house-to-house surveys of 30 monoculture and 30 diversified farmers, data on cultural management, income, and profitability were collected and analyzed. Findings revealed that older farmers predominantly engaged in both systems, with monoculture farming involving more male farmers (70%) and diversified farming having a higher proportion of female farmers (60%). Most were married and had educational attainment ranging from elementary to high school. Monoculture farmers were largely dependent on tractors (80%), mechanical seeders (75%), and herbicides (90%), whereas diversified farmers preferred manual planting (65%) and araro (plowing) (60%), leading to lower input costs. Profitability analysis showed that monoculture farmers had a higher gross profit margin ratio (0.82) and operating profit margin ratio (0.68) compared to diversified farmers (0.67 and 0.57, respectively). While monoculture farming offers higher immediate profit margins, it demands more inputs and poses environmental risks. Diversified farming, although yielding lower profit margins, promotes sustainability and cost-efficiency. These findings suggest that farmers and policymakers must balance short-term profitability with long-term ecological and economic sustainability when choosing farming systems.